2000
DOI: 10.1093/intqhc/12.3.247
|View full text |Cite
|
Sign up to set email alerts
|

Status of a health care quality review programme in South Africa

Abstract: This paper provides an overview of an accreditation programme for health care facilities in South Africa. It traces the origin of COHSASA (The Council for Health Service Accreditation of Southern Africa) which began as a pilot programme in 1992, to its current status as the only accreditation body in the country. There are brief descriptions of its structure, how it is governed, and how standards were developed and organized. The authors sketch a background of the unique sociopolitical context and legal develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In these instances, decentralisation strengthened the capacity of local organisations to negotiate with central government structures for increased resource allocation to previously neglected groups (Alves et al 2013:76). However, other authors believe that decentralisation has intensified problems of disparity in vulnerable populations, leading to poor-quality health care delivery (Regmi et al 2010:407; Whittaker et al 2000:207). According to Surender (2014:18), separating policy determinants from policy implementers in South Africa has led to a crisis in health delivery.…”
Section: Resultsmentioning
confidence: 99%
“…In these instances, decentralisation strengthened the capacity of local organisations to negotiate with central government structures for increased resource allocation to previously neglected groups (Alves et al 2013:76). However, other authors believe that decentralisation has intensified problems of disparity in vulnerable populations, leading to poor-quality health care delivery (Regmi et al 2010:407; Whittaker et al 2000:207). According to Surender (2014:18), separating policy determinants from policy implementers in South Africa has led to a crisis in health delivery.…”
Section: Resultsmentioning
confidence: 99%
“…25 It has been reported that an accreditation process may increase staff motivation and improve communication between different service units. 33 The teamwork culture is associated with the willingness of staff to undertake quality improvement initiatives. 23 Moreover, internal quality improvement strategies are inter-related at the same organisational level.…”
Section: Impacts Of Hospital Accreditationmentioning
confidence: 99%
“…Since the COHSASA programme required an initial baseline assessment against the standards, it was felt that this assessment would assist to identify significant deficiencies in the work environment that militated against safe quality service provision. 6 The evaluation process begins with the qualitative and quantitative assessment of several pre-determined criteria. Hospitals are categorised as non-compliant, partially compliant or compliant with each criterion relative to its related standard.…”
Section: Addressing the Problem -The Uah Experiencementioning
confidence: 99%